Developing Muslim Communties in the Philippines Through Transformational Leadership: An Islamic Perspective - Sapia Moalam Abdulrachman; Abdullah Sumrahadi; Badriya P. Makol (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2012)
This research concludes that development of Muslim communities in the Philippines primarily relies on local initiatives and people’s assertive character to institute behavioral reform. It entails a transformation process involving all sectors of the society in such a way that true and committed Muslim leaders will emerge to provide direction and at the same time orchestrate the development of the communities.It is therefore argued that transformational leadership is the most appropriate model that could improve the living conditions of Muslims in the Philippines Firstly, this study provides the empirical evidence that leaders and followers believe that it is through Islamic leadership that their communities can be developed. Secondly, the history of the leadership of Prophet Mohammad and his four caliphs proved that Islamic leadership is indeed transformational leadership one, hence, they deserve to be emulated by Muslims.